1976
DOI: 10.1007/bf00423314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amitriptyline and isocarboxazid on 5-hydroxytryptophan induced head twitches in mice

Abstract: Effects of amitriptyline and isocarboxazid on brain 5-HT and 5-HIAA were examined in relation to their action on 5-HTP induced head twitches. Amitriptyline reduced 5-HTP induced head twitches but isocarboxazid increased them. Both amitriptyline and isocarboxazid caused a significant increase of brain 5-HT concentration in 5-HTP treated mice. Amitriptyline also caused a significant increase of 5-HIAA concentration, while isocarboxazid reduced 5-HIAA concentration in the brains of 5-HTP treated mice. Probenecid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Although 5‐HTP‐induced head twitches are known to be mainly mediated by the 5‐HT 2A receptor, the elevated 5‐HT levels in the brains of mice induced by several types of antidepressants (e.g. fluoxetine and moclobemide) have been reported to increase the number of head twitches (Nakamura et al, ). Furthermore, our previous study showed that except for the 5‐HT 1A receptor and SERT, YL‐0919 showed no affinity for the 5‐HT 2A receptor (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although 5‐HTP‐induced head twitches are known to be mainly mediated by the 5‐HT 2A receptor, the elevated 5‐HT levels in the brains of mice induced by several types of antidepressants (e.g. fluoxetine and moclobemide) have been reported to increase the number of head twitches (Nakamura et al, ). Furthermore, our previous study showed that except for the 5‐HT 1A receptor and SERT, YL‐0919 showed no affinity for the 5‐HT 2A receptor (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%